A 24‐month metformin treatment study of children with obesity: Changes in circulating GDF‐15 and associations with changes in body weight and visceral fat. Issue 2 (23rd August 2021) - Carreras‐Badosa, Gemma; Gómez‐Vilarrubla, Ariadna; Mas‐Parés, Berta; Martínez‐Calcerrada, José‐María; Xargay‐Torrent, Silvia; Prats‐Puig, Anna; Puerto‐Carranza, Elsa; Díaz‐Roldán, Ferran; de Zegher, Francis; Ibañez, Lourdes; Bassols, Judit; López‐Bermejo, Abel
Summary: Background: Metformin treatment for 24 months in children with obesity lowers body mass index (BMI), reduces liver fat, and normalizes endocrine‐metabolic parameters. Objective: Here we study whether circulating GDF‐15 levels were raised by such metformin treatment and whether they related to changes in body weight and visceral fat in children with obesity. Methods: The study population consisted of 18 pre‐pubertal/early pubertal children with obesity who had participated in a randomized double‐blind clinical trial receiving metformin (850 mg/day) or placebo for 24 months. Circulating GDF‐15, BMI and abdominal visceral and liver fat (magnetic resonance imaging) were assessed at 0, 6, 12 and 24 months. Results: Results showed that metformin‐treated children had higher GDF‐15 levels at 6 and 12 months. Higher rises of circulating GDF‐15 associated with more loss of body weight and visceral fat. Conclusion: In conclusion, the concept that GDF‐15 is among the mediators of metformin's normalizing effects in individuals with obesity is herewith extended into childhood.